Effects of chronic exposure to cadmium and copper on the proteome profile of hemolymph in false widow spider Steatoda grossa (Theridiidae) - Kamila Wiśniewska; Małgorzata Siatkowska; Piotr Komorowski; Kinga Napieralska; Katarzyna Kasperkiewicz; Kinga Surmiak–Stalmach; Grażyna Wilczek (Ecotoxicology and Environmental Safety, 2023)
The aim of this study was to evaluate the quantitative and qualitative changes in the proteome of the hemolymph of female Steatoda grossa spiders (Theridiidae) that were chronically exposed to cadmium and copper in food and were additionally immunostimulated (phorbol 12–myristate 13–acetate (PMA); bacterial suspensions: Staphylococcus aureus (G+), Pseudomonas fluorescens (G–). It was found that the expression of nearly 90 proteins was altered in cadmium–intoxicated spiders and more than 60 in copper–exposed individuals. Regardless of the type of metal used, these proteins were mainly overexpressed in the hemolymph of the exposed spiders. On the other hand, immunostimulation did not significantly change the number of proteins with altered expression in metal–intoxicated individuals. Hemocyanin (Hc) was found to be the most abundant of the proteins identified with altered expression. In copper–intoxicated spiders, immunostimulation increased the expression of A-, E–, F–, and G–chain–containing proteins, while in the case of cadmium–intoxicates spiders, it decreased the expression of E– and A–chain–containing Hc and increased the expression of G–chain–containing Hc. Regardless of the type of metal and immunostimulant used, there was an increase in the expression of actin. In addition, cadmium increased the expression of cullin, vimentin, and ceruloplasmin. The changes observed in the expression of hemolymph proteins indicate their protective function in S. grossa (Theridiidae) spiders under conditions of metal exposure.